PENATARAN PENGEMBANGAN WAWASAN KEWIRAUSAHAAN ANGGOTA KOPERASI KRAMA BALI DI KABUPATEN KLUNGKUNG - YADNYA, I PUTU (Buletin Udayana Mengabdi; Vol 6 No 2 (2007): Volume 6 No.2 - September 2007, 2012)
ABSTARCT In order to develop entrepreneurship view of the members and the board of Koperasi Krama Bali in Klungkung regency is held a workshop with the theme “The Workshop of Developing of Entrepreneurship View of Koperasi Krama Bali (KKB) Members in Klungkung Regency. This service is held on Friday, October 13th, 2006 at Aula Pertemuan Kantor Dinas Perkebunan Kabupaten Klungkung, the workshop is attended by the supervisor of KKB, the members and the board of KKB in Klungkung regency. Total participant was 27 people. This activity was ran smoothly and welcomed by related party. The participant was serious and enthusiastic in following the material of the workshop as well as taking a part in discussion. This is caused by the curiosity of the participant in broaden the material and then it is expected to be applied in the society.